Epidemiology of Knee Sprains in Youth, High School, and Collegiate American Football Players - Clifton, Daniel R. (J Athl Train, 2017)
CONTEXT: : Variations in knee-sprain incidence among competition levels are unclear but may help inform prevention strategies in American football players. OBJECTIVE: : To describe the epidemiology of knee sprains in youth, high school, and collegiate football players. DESIGN: : Descriptive epidemiology study. SETTING: : Injury and athlete-exposure (AE) data were collected from 3 injury-surveillance programs at the youth, high school, and collegiate competition levels. PATIENTS OR OTHER PARTICIPANTS: : Data from 310 youth, 184 high school, and 71 collegiate football team-seasons were collected during the 2012 through 2014 seasons. MAIN OUTCOME MEASURE(S): : Knee-sprain rates and risks were calculated for each competition level. Injury rate ratios (IRRs) and risk ratios (RRs) compared knee-sprain rates by competition level. Injury proportion ratios (IPRs) compared differences in surgery needs, recurrence, injury mechanism, and injury activity by competition level. RESULTS: : Knee-sprain rates in youth, high school, and collegiate football were 0.16/1000 AEs, 0.25/1000 AEs, and 0.69/1000 AEs, respectively. Knee-sprain rates increased as the competition level increased (high school versus youth: IRR = 1.60; 95% confidence interval [CI] = 1.12, 2.30; collegiate versus high school: IRR = 2.73; 95% CI = 2.38, 3.96). Knee-sprain risk was highest in collegiate (4.3%), followed by high school (2.0%) and youth (0.5%) athletes. Knee-sprain risk increased as the competition level increased (high school versus youth: RR = 3.73; 95% CI = 2.60, 5.34; collegiate versus high school: RR = 2.14; 95% CI = 1.83, 2.51). Collegiate football had the lowest proportion of knee sprains that were noncontact injuries (collegiate versus youth: IPR = 0.54; 95% CI = 0.31, 0.95; collegiate versus high school: IPR = 0.59; 95% CI = 0.44, 0.79) and the lowest proportion that occurred while being tackled (collegiate versus youth: IPR = 0.44; 95% CI = 0.26, 0.76; collegiate versus high school: IPR = 0.71; 95% CI = 0.51, 0.98). CONCLUSIONS: : Knee-sprain incidence was highest in collegiate football. However, level-specific variations in the distributions of knee sprains by injury activity may highlight the need to develop level-specific policies and prevention strategies that ensure safe sports play.